Aesthetics and meaning within the circular design discourse: an analysis based on design projects - Costa, Nina (2024)
Design is recognised as a crucial driver of innovation and a facilitator of the transition to a circular economy. While there are numerous strategies to support circular design practices, many tend to prioritise management and engineering processes, neglecting design's aesthetic dimension and its role as a cultural mediator. This research paper aims to revisit the role of design in the circular economy, emphasising its aesthetic and meaning dimensions, and exploring the potential of circular design to trigger socio-cultural change. It analyses existing literature and examines 14 design projects developed within a higher education institution in Portugal, using an abductive approach. The paper develops a conceptual matrix that establishes connections between material function, meaning, and sustainability aesthetics, forming a continuum of design approaches. The findings indicate that material exploration and transformation often shape the ethos of the project, while design intention and aesthetics are emergent components. Moreover, the potential to reach a significant human impact is still quite limited. These results indicate the need to rebalance the ontological contours of the discipline within circular discourse, going beyond functionalism.